BUNYI /O/ DIALEK KAMPAR BERASAL DARI / / DIALEK RIAU KEPULAUAN: BENARKAH? - Zainal Abidin (Balai Bahasa Provinsi Riau, 2012)
The object ive of this research is to find out the origin of phone / / in BMDK. In order to reach the goal, this research uses the data in forms of 100 words listed in the Swadesh Form. The Data were obtained by the mapping team of local language of Balai Bahasa Provinsi Riau. The data were analyzed with descriptive method, dialectology theory and linguistic history. The research findings show that phone / / in BDMK does not come from /